Acquisition of Arabic Language based on Stephen Krashen's Theory in the Arabic Camp Activities - Suci Ramadhanti Febriani (EL-IBTIKAR: Jurnal Pendidikan Bahasa Arab, 2020)
The determining factors for a person's success in language vary widely. One of them is the acquisition of a person's language which is a source of skill in producing the language itself. There is often a contradiction between the terms language acquisition and language learning. Psycholinguistics experts view that language acquisition only occurs for the first language, but this is different from Stephen Khrasen who stated that language acquisition can be obtained for foreign languages. On this basis, researchers studied the implementation of foreign language acquisition at MAN 1 Padang during the Arabic Camp activity, based on Stephen Khrasen's theory. Researchers used a qualitative approach with a case study research design. Data collection includes observation, interviews and documentation with data analysis techniques using data triangulation. The results showed that the acquisition of a second language was influenced by good input and processes such as the all-day language environment and good monitoring processes from the tutors. All of this is in accordance with Stephen Khrasen's theory which will provide maximum output in producing Arabic like native speakers even though it is still in a simple sentence formation system in the Camp environment.